Die lateinische Sprache in der Musik des 20. Jahrhunderts II: Krzysztof Pendereckis "Dies Irae" - Schubert, Werner (International journal of musicology, 1996)
In our century, Latin has by no means lost its attractiveness for composers and listeners. The gamut of Latin texts set to music became even larger: composers turned to non-canonical liturgies, to non-Christian Latin and even to completely new Latin texts expressly written for the given purpose. This was the case with Strawinsky's Oedipus Rex, a rare piece in its kind. Initially, this practice found few followers, except for Carl Orff who, for the framing parts of his Catulli Carmina, provided a home-made Latin text in the vein of Plautus. It was left, however, to Krzysztof Penderecki to adopt, in his Dies irae, a method comparable to Strawinsky's. Yet, unlike the latter, he avoided radical innovation: By adopting for his work the title of a famous Latin sequence (Dies irae), he directed his listeners' expectations towards a determined goal. Furthermore, he incorporated into his work original Latin quotations from the Vulgate and Greek lines from Aeschylus' Eumenides.
Elektronische Reproduktion der Druckausgabe
Gesehen am 02.11.2023